Research and Development of Information and Communication Technology-based Home Blood Pressure Monitoring from Morning to Nocturnal Hypertension - Kazuomi Kario; Naoko Tomitani; Yuri Matsumoto; Haruna Hamasaki; Yukie Okawara; Maiko Kondo; Ryoko Nozue; Hiromi Yamagata; Ayako Okura; Satoshi Hoshide (Ubiquity Press, 2016)
Asians have specific characteristics of hypertension (HTN) and its relationship with cardiovascular disease. The morning surge in blood pressure (BP) in Asians is more extended, and the association slope between higher BP and the risk for cardiovascular events is steeper in this population than in whites. Thus, 24-hour BP control including at night and in the morning is especially important for Asian patients with HTN. There are 3 components of "perfect 24-hour BP control": the 24-hour BP level, adequate dipping of nocturnal BP (dipper type), and adequate BP variability such as the morning BP surge. The morning BP-guided approach using home BP monitoring (HBPM) is the first step toward perfect 24-hour BP control. After controlling morning HTN, nocturnal HTN is the second target. We have been developing HBPM that can measure nocturnal BP. First, we developed a semiautomatic HBPM device with the function of automatic fixed-interval BP measurement during sleep. In the J-HOP (Japan Morning Surge Home Blood Pressure) study, the largest nationwide home BP cohort, we successfully measured nocturnal home BP using this device with data memory, 3 times during sleep (2, 3, and 4 am), and found that nocturnal home BP is significantly correlated with organ damage independently of office and morning BP values. The second advance was the development of trigger nocturnal BP (TNP) monitoring with an added trigger function that initiates BP measurements when oxygen desaturation falls below a variable threshold continuously monitored by pulse oximetry. TNP can detect the specific nocturnal BP surges triggered by hypoxic episodes in patients with sleep apnea syndrome. We also added the lowest heart rate-trigger function to TNP to detect the "basal nocturnal BP," which is determined by the circulating volume and structural cardiovascular system without any increase in sympathetic tonus. This double TNP is a novel concept for evaluating the pathogenic pressor mechanism of nocturnal BP. These data are now collected using an information and communication technology (ICT)-based monitoring system. The BP variability includes different time-phase variability from the shortest beat-by-beat, positional, diurnal, day-by-day, visit-to-visit, seasonal, and the longest yearly changes. The synergistic resonance of each type of BP variability would produce great dynamic BP surges, which trigger cardiovascular events. Thus, in the future, the management of HTN based on the simultaneous assessment of the resonance of all of the BP variability phenotypes using a wearable "surge" BP monitoring device with an ICT-based data analysis system will contribute to the ultimate individualized medication for cardiovascular disease.